Застосування методів неруйнівного контролю в дефектоскопії - Егиян, Г. Д.; Карнаушенко, В. П. (ХНУРЕ, 2019)
Most important in material inspection is noninvasive techniques to determine the integrity of a material and component. Eddy Currents are most effectively used to check for cracking located at the surface of metals such as rails. Figure 1 shows the different inspection areas covered by eddy currents and ultrasonic. It is important to emphasize at this stage that ultrasonics and eddy currents are complementary inspection methods and should not be used exclusively of one another.
Keywords: дефектоскопія; неруйнівний контроль